Overwhelmed [compact disc, unabridged] : work, love, and play when no one has the time - Schulte, Brigid, 1962- (Brilliance Audio, 2014)
Can working parents in America ever find true leisure time? Brigid Schulte provides a map of the stresses that have ripped leisure to shreds, and a look at how to put the pieces back together. She speaks to neuroscientists, sociologists, and hundreds of working parents to tease out the factors contributing to the collective sense of being overwhelmed, seeking insights, answers, and inspiration.